Efficacy of systemic antibiotics in nonsurgical periodontal therapy for diabetic subjects: a systematic review and meta-analysis - Souto, Maria Luisa S.; Rovai, Emanuel S.; Ganhito, Juliana A.; Holzhausen, Marinella; Chambrone, Leandro; Pannuti, Cláudio M. (International dental journal, 2018)
Objectives: To evaluate the effects of systemic antibiotics as adjuncts to nonsurgical periodontal treatment (NSPT), as opposed to using NSPT alone, on periodontal clinical parameters of diabetic patients with periodontitis. Materials and methods: Randomised controlled trials with a follow-up of 3 months or more, assessing the effects of NSPT in combination with antibiotics, in diabetic patients with periodontitis were included. Trials published up to August 2016 were identified from MEDLINE, EMBASE and LILACS databases. Meta-analyses were conducted to determine changes in clinical attachment level (CAL), probing pocket depth (PPD), bleeding on probing (BOP) and gingival index (GI). Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed in this review. Results: Of the 164 papers potentially admissible to this systematic review, 15 articles on 11 randomised clinical trials were considered as eligible. The results of the meta-analyses presented a modest additional benefit of 0.14 mm (95% confidence interval: 0.08–0.20) in reducing PPD but no further benefit in CAL gain. Conclusion: When the data for all antibiotic protocols were considered together for the treatment of periodontitis patients with DM, a significant, albeit small, reduction of PPD and no improvement in CAL gain was observed. When the antibiotic protocols were analysed separately, the combination of amoxicillin plus metronidazole yielded the best results for PPD.